Computer safety, reliability, and security : 34th International Conference, SAFECOMP 2015, Delft, the Netherlands, September 23-25, 2015, Proceedings /: 34th International Conference, SAFECOMP 2015, Delft, the Netherlands, September 23-25, 2015, Proceedings. (2015) - Unknown
No abstract available